ENGLISH HOMONYMS AND THEIR MEANINGS - Azimova Husnora Sunnatilli qizi (Web of Journals Publishing, 2025)
The article delves into the rich landscape of English homonyms, emphasizing the importance of understanding subtle differences in meaning, usage, and context. It begins by defining what homonyms are—words that share the same spelling or pronunciation but have different meanings. The article also defines homonyms and explains their role in enhancing vocabulary and improving communication. It highlights how homonyms can add variety to language, making writing and speech more engaging.
Keywords: English homonyms; different connotations; enhancing vocabulary exchange; engaging; Resources for learning; homonyms for effective communication.